Outsourcing at the University of the Witwatersrand: reasons and rationale - Dumba, Noreen Nyasha (My University, 2015)
Outsourcing has been a common trend over the years and the University of Witwatersrand followed suit in 2001 under Colin Bundy (the ex-Vice Chancellor). Though outsourcing can be beneficial to enterprises it can have negative effects on the workers. The aim of this study was to develop an understanding into the reasons and rationale of the outsourcing decision at the University of Witwatersrand focusing on cleaning services. Secondary sources of data were used in the form of official reports in the public domain. The results of the study indicate that the University of Witwatersrand was able to save from the proportions of operational costs reduced through outsourcing and this enabled significant profits at the expense of exploited outsourced workers. However due to transaction costs, cost creep, coordination efficiency, loss of tacit skills and organisational memory which the university has incurred, costs will increase and organisational efficiency will not be achieved.
Thesis (M.Com. (Development Theory and Policy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2014.